Emergence and Potential Extinction of Genetic Lineages of Human Metapneumovirus between 2005 and 2021 - Kevin Groen; Stefan van Nieuwkoop; Adam Meijer; Bas van der Veer; Jeroen J. A. van Kampen; Pieter L. Fraaij; Ron A. M. Fouchier; Bernadette G. van den Hoogen (mBio, 2023)
ABSTRACT Human metapneumovirus (HMPV) is one of the leading causes of respiratory illness (RI), primarily in infants. Worldwide, two genetic lineages (A and B) of HMPV are circulating that are antigenically distinct and can each be further divided into genetic sublineages. Surveillance combined with large-scale whole-genome sequencing studies of HMPV are scarce but would help to identify viral evolutionary dynamics. Here, we analyzed 130 whole HMPV genome sequences obtained from samples collected from individuals hospitalized with RI and partial fusion (n = 144) and attachment (n = 123) protein gene sequences obtained from samples collected from patients with RI visiting general practitioners between 2005 and 2021 in the Netherlands. Phylogenetic analyses demonstrated that HMPV continued to group in the four sublineages described in 2004 (A1, A2, B1, and B2). However, one sublineage (A1) was no longer detected in the Netherlands after 2006, while the others continued to evolve. No differences were observed in dominant (sub)lineages between samples obtained from patients with RI being hospitalized and those consulting general practitioners. In both populations, viruses of lineage A2 carrying a 180-nucleotide or 111-nucleotide duplication in the attachment protein gene became the most frequently detected genotypes. In the past, different names for the newly energing lineages have been proposed, demonstrating the need for a consistent naming convention. Here, criteria are proposed for the designation of new genetic lineages to aid in moving toward a systematic HMPV classification. IMPORTANCE Human metapneumovirus (HMPV) is one of the major causative agents of human respiratory tract infections. Monitoring of virus evolution could aid toward the development of new antiviral treatments or vaccine designs. Here, we studied HMPV evolution between 2005 and 2021, with viruses obtained from samples collected from hospitalized individuals and patients with respiratory infections consulting general practitioners. Phylogenetic analyses demonstrated that HMPV continued to group in the four previously described sublineages (A1, A2, B1, and B2). However, one sublineage (A1) was no longer detected after 2006, while the others continued to evolve. No differences were observed in dominant (sub)lineages between patients being hospitalized and those consulting general practitioners. In both populations, viruses of lineage A2 carrying a 180-nucleotide or 111-nucleotide duplication in the attachment protein gene became the most frequently detected genotypes. These data were used to propose criteria for the designation of new genetic lineages to aid toward a systematic HMPV classification.